FORMATION OF MECHANISMS FOR REDUCING INVESTMENT RISKS IN THE BAKING INDUSTRY THROUGH THE INTRODUCTION OF INNOVATIVE TECHNOLOGIES - NEMASHKALO, Karina; DANKO, Yuriy; ZELENYAK, Vasyl; LYZOHUB, Andrii; BENYK, Maksym (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article comprehensively analyzes investment risks in the Ukrainian bakery industry, which significantly affect its financial stability and competitiveness. It investigates the main challenges, particularly the economic, financial, production, regulatory, and market factors that shape the industry's general investment environment. It is determined that fluctuations in raw material prices, exchange rate instability, rising energy costs, and high competition are key risks that complicate investment attraction and production modernization. Considerable attention is paid to studying the potential of innovative technologies in minimizing these risks. It is found that automation of production processes, implementation of energy-efficient technologies, digitalization of management solutions, and use of the latest quality control systems can significantly reduce costs, increase productivity, and ensure the stability of enterprises. The possibilities of using artificial intelligence, big data analytics, and product life cycle management to optimize production processes and increase environmental responsibility are investigated.The main risks associated with innovation processes are analyzed, particularly the need for significant capital investments, the possibility of technical incompatibility of new solutions with existing production capacities, and the risk of inconsistency with consumer expectations. Strategic approaches to investment risk management are proposed, including a comprehensive analysis of threats, forecasting changes in the market environment, and developing adaptation mechanisms.As part of the study, a structural-level risk classification scheme has been developed. This scheme allows for a systematic assessment of threats and the development of effective management solutions. The proposed scheme divides risks into direct, indirect, and background, allowing for determining the level of their impact on bakery enterprises and selecting appropriate minimization mechanisms. It is concluded that for the further development of Ukraine's bakery industry, it is necessary to actively introduce innovative technologies, expand the digital capabilities of production process management, and form strategies for adapting to market challenges. This will help increase the industry's competitiveness, attract new investments, and ensure its sustainable development in the long term.
Keywords: investment risks; bakery flour; innovative technologies; risk management; investment receipts